2014
DOI: 10.1371/journal.pone.0105533
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR1-Positive Macrophages Facilitate Liver Repair and Sinusoidal Reconstruction after Hepatic Ischemia/Reperfusion Injury

Abstract: Liver repair after acute liver injury is characterized by hepatocyte proliferation, removal of necrotic tissue, and restoration of hepatocellular and hepatic microvascular architecture. Macrophage recruitment is essential for liver tissue repair and recovery from injury; however, the underlying mechanisms are unclear. Signaling through vascular endothelial growth factor receptor 1 (VEGFR1) is suggested to play a role in macrophage migration and angiogenesis. The aim of the present study was to examine the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 47 publications
2
41
0
1
Order By: Relevance
“…Moreover, VEGF's binding to LSECs also triggers the release of HB‐EGF through an overlapping VEGFR‐1/2–based mechanism . Although VEGF has not been shown to directly up‐regulate EGF transcript expression through either VEGFR‐1 or VEGFR‐2, VEGFR‐1–expressing macrophages secrete EGF and increasing VEGFR‐1 signaling has been shown to up‐regulate EGF expression in VEGF‐stimulated macrophages . Consistent with this evidence, we observed that VEGF gene delivery prior to EPC transplantation was able to increase the expression of all 4 hepatotrophic factors (ie, EGF, HB‐EGF, HGF, and TGF‐α) in post‐OLT–induced HIRI.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Moreover, VEGF's binding to LSECs also triggers the release of HB‐EGF through an overlapping VEGFR‐1/2–based mechanism . Although VEGF has not been shown to directly up‐regulate EGF transcript expression through either VEGFR‐1 or VEGFR‐2, VEGFR‐1–expressing macrophages secrete EGF and increasing VEGFR‐1 signaling has been shown to up‐regulate EGF expression in VEGF‐stimulated macrophages . Consistent with this evidence, we observed that VEGF gene delivery prior to EPC transplantation was able to increase the expression of all 4 hepatotrophic factors (ie, EGF, HB‐EGF, HGF, and TGF‐α) in post‐OLT–induced HIRI.…”
Section: Discussionsupporting
confidence: 76%
“…Following liver injury, both hepatocytes and HSCs have been shown to quickly up‐regulate their VEGF secretion in response to cytokines as well as hypoxia in order to support hepatic recovery . VEGF acts on its target cells via 2 key tyrosine kinase receptors named VEGFR‐1 (alternatively fms related tyrosine kinase 1 [Flt‐1]) and VEGFR2 (alternatively fetal liver kinase‐1 [Flk‐1] and kinase insert domain receptor [KDR]) . Because increased VEGF expression has been shown to be linked to both VEGFR‐1 up‐regulation on hepatocytes as well as VEGFR‐1 and VEGFR‐2 up‐regulation on LSECs, here we successfully confirmed the effective liposomal delivery of the VEGF gene to the target liver tissue of the VEGF‐treated groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the VEGFR1 functions that have been identified are in non-ECs (33,34,35,36,37,38) , and endothelial specific VEGFR1 functions remain uncertain. Our experimental data showed that VEGF 165 b-inhibition induces VEGFR1-activation not VEGFR2 or its downstream signaling in Balb/c ischemic muscle.…”
Section: Discussionmentioning
confidence: 99%
“…By using VEGFR1 tyrosine kinase knockout mice, Ohkubo H et al found that VEGFR1-expressing macrophages were recruited to the liver during hepatic ischemia/reperfusion and contribute to liver repair and sinusoidal reconstruction through regulating expression of pro-angiogenic factors. This study demonstrated that VEGFR1 activation is a potential therapeutic strategy for promoting liver repair and sinusoidal restoration after acute liver injury [ 22 ]. Coulon S et al demonstrated that the blockage of VEGFR2 could attenuate steatosis and inflammation in a diet-induced mouse model for nonalcoholic steatohepatitis.…”
Section: Discussionmentioning
confidence: 99%